Experimental investigation of end milling of titanium alloys with polycrystalline diamond tools. (August 2014) - Pan, Wencheng; Kamaruddin, Adam; Ding, Songlin; Mo, John
The low thermal conductivity and high chemical reactivity of titanium alloys result in a short tool life in the milling process. This article investigates the performance of polycrystalline diamond tools in the end milling of titanium alloys (Ti6Al4V) by using small customized cutting tools. The relationship between cutting force and cutting parameters was analysed; tool life, tool wear, and causes that lead to tool failure were discussed. To analyse tool wear and cutting temperatures, residual chemical components on the cutting tool were examined with X-ray diffraction method, while surface integrity of cutting tools was inspected based on the images taken by the scanning electrical microscope. Finite element analysis models were developed to simulate the initiation of cracks under different loading cycles. Through cutting experiments, it was found that brittle chipping and fatigue were the two major modes of failure, and feed rate was the dominant factor that causes large cutting forces.